Суралцагчдад шинэ үг хэллэгийг эзэмшүүлэх нь: How to teach new words and phrases to the students - B., Ganchuluun (Mongolian Journal of Foreign Languages and Cultures, 2023)
Vocabulary for foreign language is a major “building material”. Researchers think that if acquired word resource was not sufficient it’s difficult to gain other language properties. To acquire new words together Chinese students are required to memorize things such as a word pronunciation and harmony, chinese charecter scratch and meaning in complex. Therefore, we aimed to give briefly on this article how to teach new words and phrases to students and increase their word resource based on the scientist research and experiments.